ダイ15ジタイ ヤマト リョコウ ホウコク - 矢内, 桂三; ヤナイ, ケイゾウ; 金子, 信吾; カネコ, シンゴ; 小堺, 秀男; コザカイ, ヒデオ; 寺井, 啓; テライ, ケイ; YANAI, Keizo; KANEKO, Shingo; KOZAKAI, Hideo; TERAI, Kei (国立極地研究所, 1976)
P(論文) From October 25, 1974 to January 17, 1975, the traverse for meteorite search were made from Syowa Station to Yamato Mountains via Mizuho Camp. The traverse party consisted of one geologist, one mechanics, one cook and one field logistics of the 15th Japanese Antarctic Research Expedition (1973-1975). A total of 663 meteorites were collected after a systematic search for the Yamato meteorites in the bare ice area of the Yamato Mountains, East Antarctica. This report are described the details of logistics aspects, namely, planning, itinerary, operations of the oversnow vehicles, food rations, equipments and radio communications for the Yamato traverse, but research activities of meteorite search are describe other paper by K. YANAI (Antarct. Rec., 56, 70, 1976). departmental bulletin paper